O dualismo grafite vs pichação : arte grafite, tagging, pichação e pixo - Araújo, Marcos Antônio Cruz de (2015)
With this research, we have sought to explore the discursivity and historicity of Graffiti by means of the discursive genre known as tag, which is a kind of stylized signature, weaving a discourse analysis over the concrete enunciates found and collected as corpus throughout the region of Grande Vitoria – ES. This procedure has been brought forth with the purpose of understanding how Brazilian society has comprised the dicotomy “Grafite/Pichação” within its discursive formation. Key-words of Discourse Analysis (DA) such as ideology, subject, history and discursive memory have served us as theoretical support, as well as to compare it with a previous analysis about the ocupation-invation opposition. The relation of the tag genre with the concepts that were mentioned above - which took place along with the field research (interviews and gathering of textual material with the local graffiti scene) - have allowed us to discern how a discursive analysis differs from the common sense built around such a dicotomy, which materializes on the enunciation plan a conflict that exists on the ideological plan. Summarily, as we put through the lens of analysis a historical and discursive point of view about the subject, we have exposed the perspective from certain social movements that have graffiti-tagging as a practice, disagreeing from such an opposition between those two terms.